1992
DOI: 10.1007/bf01187497
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of the non-myelotoxic antitumour agent of plant origin, Thaliblastine, on two human glioma cell lines

Abstract: The antiproliferative activity of the non-myelotoxic antitumour agent of plant origin, Thaliblastine, on two human glioma cell lines is described. Thaliblastine was added once one day following start of culture; proliferation was monitored over 7 days. The antiproliferative activity of Thaliblastine was strongly dependent on concentration and time of incubation. The ID50 of Thaliblastine in T406 and GW27 glioma lines was 5.1 micrograms/ml and 8.2 micrograms/ml (7.0 microM and 11.2 microM), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This molecule was found to have significant biological activity against the Walker 256 carcinoma and antiproliferative activity on a broad range of human and animal cell lines in vitro and in vivo. 4,5 Initial clinical trails on this compound appeared encouraging, [4][5][6][7][8][9] however phase II clinical trials stopped after no antitumour effect was observed. 7,9 Inspired by the structure and biological activity of thalicarpine we became interested in the synthesis of the novel laudanosine dimers of the type 2 and 3 (Figure 1), in which two laudanosine units are linked at C-2' through a two or three-carbon linker (alkane, alkene or alkyne).…”
Section: Introductionmentioning
confidence: 99%
“…This molecule was found to have significant biological activity against the Walker 256 carcinoma and antiproliferative activity on a broad range of human and animal cell lines in vitro and in vivo. 4,5 Initial clinical trails on this compound appeared encouraging, [4][5][6][7][8][9] however phase II clinical trials stopped after no antitumour effect was observed. 7,9 Inspired by the structure and biological activity of thalicarpine we became interested in the synthesis of the novel laudanosine dimers of the type 2 and 3 (Figure 1), in which two laudanosine units are linked at C-2' through a two or three-carbon linker (alkane, alkene or alkyne).…”
Section: Introductionmentioning
confidence: 99%
“…This molecule was found to have significant biological activity against the Walker 256 carcinoma and antiproliferative activity on a broad range of human and animal cell lines in vitro and in vivo. 4,5 Initial clinical trails on this compound appeared encouraging, [4][5][6][7][8][9] however phase II clinical trials stopped after no antitumour effect was observed. 7,9 Inspired by the structure and biological activity of thalicarpine we became interested in the synthesis of the novel laudanosine dimers 2 and 3, in which two laudanosine units are linked via a C-2' biaryl bond, and an examination of their cytotoxicities on cancer cell lines.…”
mentioning
confidence: 99%
“…Many species of the genus Thalictrum are often used in anti-inflammation, anti-virus, antibacterial, antitumor and hypertension treatments. They contain various kinds of bioactive components that show antirumor activities both in vitro [6], [7], [8] and in vivo [9], [10], [11].…”
mentioning
confidence: 99%